Surgical management combined with leukocyte and platelet rich fibrin (L-PRF) concentrate in the medication-related osteonecrosis of the jaws treatment - case report - Rodrigues, Bruno Teixeira Gonçalves; Pinheiro, Giulianna Lima; Prado, Roberto; Freire, Nathália de Almeida; Israel, Mônica Simões (Journal of Oral Diagnosis, 2021)
Medication-related osteonecrosis of the jaws (MRONJ) is described as an area of non- healing necrotic bone in the maxillofacial region for more than an eight-week period in patients who have received antiresorptive or antiangiogenic agents treatment, with no history of radiotherapy or metastatic disease to the jaws. A 68-year old woman medicated with oral sodium alendronate for a five-year period treating osteoporosis, presented with a painful necrotic bone exposure in the right mandible area close to the first premolar. Panoramic radiography revealed the presence of osteosclerosis and osteolysis in the area. Clinical and radiographic diagnosis was of MRONJ and antibiotic and analgesic therapy were prescribed before the surgery. Under general anesthesia, it was performed the necrotic bone curettage and use of peripheral ostectomy with a round burr in order to achieve bleeding-bone prior to the application of L-PRF membranes in the site. A two-year follow- up showed mucosa healing and at panoramic radiograph, no signs of sequestrum could be observed and no symptoms. Patient remain in clinical and radiographic follow-up with no recurrence. Therefore, the adjuvant therapy using L-PRF membranes is effective in many cases of MRONJ and should be considered as a therapeutic alternative.